alpha-Tocopherol supplementation reduces inflammation and apoptosis in high cholesterol mediated nonalcoholic steatohepatitis - SÖZEN, AHMET ERDİ; ŞAHİN, ALİ; KARTAL ÖZER, NESRİN (WILEY, 2021)
Inflammation and apoptosis signaling are crucial steps in the progression from nonalcoholic fatty liver disease (NAFLD) to nonalcoholic steatohepatitis (NASH). Alpha-tocopherol, the most active form of vitamin E, is an important modulator of signaling mechanisms, but its involvement to cholesterol-induced NASH pathogenesis remains poorly defined. Herein we have reported a novel effect of alpha-tocopherol in the transition from hepatic steatosis to NASH. High cholesterol diet alone (without alpha-tocopherol) in rabbits elevated NASH development as indicated by increased inflammatory response, apoptotic activity and liver fibrosis. Such elevation results from induction of signaling mechanisms since the expressions of IL1 beta, phospho c-Jun/c-Jun ratio, JNK, caspase 9, CHOP and Bax were increased, and recruitment of macrophage, alpha-smooth muscle actin (alpha-SMA) and COL1A1 into the liver tissue were induced. Alpha-tocopherol supplementation inhibited inflammatory response, apoptosis and fibrosis development without affecting lipid accumulation in high cholesterol-induced NASH. Specifically, alpha-tocopherol lowered the inflammatory level as observed by reduced macrophage infiltration and JNK/c-Jun signaling. Lower inflammatory status co-occurred with the reduction of CHOP and Bax expressions as well as fibrosis-related COL1A1 and alpha-SMA levels. Taken together, alpha-tocopherol supplementation inhibits cholesterol-induced NASH development by lowering JNK/c-Jun/inflammation axis in addition to JNK/CHOP/apoptosis signaling, which might contribute to resistance against NAFLD/NASH transition.
Keywords: apoptosis; fibrosis; high cholesterol diet; inflammation; NASH; alpha-tocopherol; FATTY LIVER-DISEASE; HEPATIC STELLATE CELLS; OXIDATIVE STRESS; VITAMIN-E; LIPID OXIDATION; C-JUN; EXPRESSION; AUTOPHAGY; NAFLD; ACIDS